Epidermal Proliferation and Differentiation in Ichthyosis Vulgaris - Nopriyati; Deddy Deddy; Rusmawardiana; Mutia Devi (HM Publisher, 2021)
A B S T R A C TEpidermal proliferation and differentiation is a physiological process which playscrucial role in protecting human body from external environment. Ichthyosisvulgaris is a disease caused by disruption of epidermal differentiation process.Disrupted of profilaggrin conversion to filaggrin caused by mutations from thefilaggrin gene (FLG) located on chromosome 1q21. Recently, caused of ichthyosisvulgaris is mutation of the CASP14 gene on chromosome 19p13.12 which producescaspase-14, is involved in the proteolytic degradation of filaggrin. Clinicalmanifestations of ichthyosis vulgaris are hyperlinear palmar and plantar, keratosispilaris, xerosis, and localized or generalized scaling of the skin. Application ofemollients, humectants and keratolytic agents are the main treatment of ichthyosisvulgaris. Further research on caspase-14 as a therapeutic target is needed in thetreatment of ichthyosis vulgaris.